The urban from the anthropology in San Marcos - Pimentel Sánchez, Nekson (2017)
This article intends to make a state of the art about the studies of the urban from the anthropology at the National University of San Marcos (San Marcos, hereinafter), through the analysis of empirical investigations that include the theses of Bachiller, Licenciatura, Mastership and Doctorate from the first decades to 2012, which together form part of the process of constituting and consolidating anthropology in the Dean of America. It includes the different topics developed that obey our own professional and academic insertion, the theoretical and methodological influences in each of the productions, as well as the characteristics of the research in the different stages.